IL-27 overexpression alleviates inflammatory response in allergic asthma by inhibiting Th9 differentiation and regulating Th1/Th2 balance. (3rd September 2022) - Xiong, Peng; Liu, Tonglin; Huang, Hao; Yuan, Yi; Zhang, Wendi; Fu, Lina; Chen, Yu
Abstract: Objective: To investigate the effect of IL-27 on Th9 differentiation and Th1/Th2 balance. Methods: C57BL/6 (B6) mice were treated with ovalbumin to establish an allergic asthma (AA) model and subjected to IL-27 overexpression (OV) and empty vector (EV). Hematoxylin-eosin (HE) staining was performed to observe lung tissue inflammation. Flow cytometry was carried out to evaluate the percentage of Th9, Th1, and Th2 cells. The expression of IL-27, IL-27R, IL-9, T-bet, IFN-γ, and IgE was evaluated by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA). Western blot was conducted to observe the expression of pSTAT-1 and pSTAT-3. Results: Compared with the Model group, the number of Th1 cells in the Model + OV group increased significantly ( p < .05), while those of Th9 and Th2 cells decreased significantly ( p < .05). The expression of IL-27, IL-27R, and IFN-γ in blood serum was increased ( p < .05), and that of IL-9 and IgE was significantly decreased in the Model + OV group compared to the Model ( p < .05). Western blot revealed that Model + OV exhibited lower expression of pSTAT-3 than that in the Model and Model + EV groups ( p < .05), while pSTAT-1 expression was significantly increased ( p < .05). Inflammatory infiltration in the Model + OV group was significantly reduced, and there was no significant difference between the Model and Model + EV groups. Conclusions: IL-27 OV inhibits Th9 differentiation and regulates the imbalance of Th1/Th2, thereby alleviating inflammatory response in AA. The findings suggest that IL-27 OV may be a potential strategy for clinical treatment of AA.